2022
DOI: 10.1007/s10803-021-05402-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Geographic Access to Board Certified Behavior Analysts Among Children with Autism Spectrum Disorder, 2018–2021

Abstract: Research has documented inequities in geographic access to Board Certified Behavior Analysts (BCBAs) among children with autism spectrum disorder (ASD). However, research on their accessibility is outdated. Between July 1, 2018 and July 1, 2021 the number of BCBAs in the U.S. increased by 65%, from 27,320 to 45,103. In this study we examined trends in geographic access to BCBAs among children with ASD between 2018 and 2021. The sample included all U.S. counties in 50 states and D.C. (N = 3138). Using GIS softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
6
0
3
Order By: Relevance
“…As a result, this training approach may present an unreasonable time or financial burden for some human service organizations, or some organizations may not have enough well‐trained individuals to implement BST (DiGennaro Reed et al, 2013; Gerencser et al, 2020; Shapiro & Kazemi, 2017). However, with the immense need for services and the limited number of qualified behavior analysts to provide training (Behavior Analyst Certification Board, 2023; Yingling et al, 2021; Yingling et al, 2022), it is no wonder that the major research trends we observed in the literature were related to improving the efficacy and efficiency of BST for training individuals to implement DTT procedures. This finding is identical to the research themes in the general BST literature (Erath & DiGennaro Reed, 2020; Gerencser et al, 2020; Marano et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this training approach may present an unreasonable time or financial burden for some human service organizations, or some organizations may not have enough well‐trained individuals to implement BST (DiGennaro Reed et al, 2013; Gerencser et al, 2020; Shapiro & Kazemi, 2017). However, with the immense need for services and the limited number of qualified behavior analysts to provide training (Behavior Analyst Certification Board, 2023; Yingling et al, 2021; Yingling et al, 2022), it is no wonder that the major research trends we observed in the literature were related to improving the efficacy and efficiency of BST for training individuals to implement DTT procedures. This finding is identical to the research themes in the general BST literature (Erath & DiGennaro Reed, 2020; Gerencser et al, 2020; Marano et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In underserved populations, early diagnosis and treatment are negatively affected by complex racial‐ethnic and socio‐demographic, including immigrant, factors (i.e. (Durkin et al., 2010 ; Kelly et al., 2019 ; Khanlou et al., 2017 ; Yingling & Bell, 2019 ; Yingling et al., 2022 )). There are racial‐ethnic and neighborhood inequities in the age of treatment receipt (Yingling & Bell, 2019 ).…”
Section: Limitations and Important Considerations For Future Researchmentioning
confidence: 99%
“…There are racial‐ethnic and neighborhood inequities in the age of treatment receipt (Yingling & Bell, 2019 ). Relatedly, there is both unequal access to services and therapists (Yingling et al., 2022 ) and inequitable utilization of services, with a smaller proportion of Black and Latino as well as low socio‐economic status children receiving services (Yingling et al., 2019 ). In particular, among children with IQ < 70 and ASD diagnosis, there is a 6‐month lag in the age at first autism diagnosis for African American/Black infants reported in (Maenner et al., 2020 ).…”
Section: Limitations and Important Considerations For Future Researchmentioning
confidence: 99%
“…Tomlinson et al 1 explored the use of telehealth for behavioural support in individuals with intellectual and developmental disabilities (IDD). They examined the perspectives of family carers and professionals on this approach, considering the need for accessible interventions and the impact of the COVID-19 pandemic 2 3. Telehealth, using digital communication technologies like video conferencing and remote monitoring, expands significantly during COVID-19 pandemic to ensure continued access to care 3.…”
Section: Contextmentioning
confidence: 99%